The effect of the national brand on high-tech exports in selected countries - Abolfazl Shahabadi; Shiva Amjadian; Samineh Ghasemifar; Masoume Shafieian (Journal of Innovation and Entrepreneurship, 2023)
High-tech exports play a crucial role in the growth and prosperity of the national economy due to higher added value and higher profitability. However, gaining a competitive advantage and increasing high-tech exports is arduous because of the highly competitive environment in global markets. In addition, increasing the value of the national brand through the improvement of foreign customers' mental image of products made in a specific country, can play an undeniable role in the improvement of customer's loyalty and growth of high-tech exports. In this paper, we evaluate the impact of the national brand on high-tech exports in 12 countries with the most valuable nation-brand, using panel data and a generalized method of moments (GMM), during the period 2015-2021. The results showed the positive and significant impact of the national brand in this group. It means that although improvement of the national brand stimulates the demand for high-tech products from foreign customers, countries that have had more capacity to increase the production and supply of these products have been more successful in meeting the created surplus demand. Therefore, developing countries should take action to improve the national brand, by moving towards a knowledge-based economy, and at the same time, they have to increase their capacity of production and supply of high-tech products to be able to meet the demands of these products in global markets.
Keywords: F14; F31; K11; M16; 650; Intellectual property rights; High-tech exports; National brand; Real exchange rate